Intersecting alcohol use and depression impedes HIV treatment in the rural South, USA. Issue 3 (3rd July 2022) - Kalichman, Seth C.; Katner, Harold; Banas, Ellen; Hill, Marnie; Kalichman, Moira O.
Abstract: This study tested the hypothesis that the co-occurrence of alcohol use and depressive symptoms predicts HIV suppression and antiretroviral therapy (ART) adherence among people living with HIV. Baseline cross-sectional results showed a significant interaction between depressive symptoms and alcohol use in predicting HIV suppression; individuals who drank more alcohol and had higher depressive symptoms demonstrated poorer HIV suppression relative to those who had fewer depressive symptoms. In a one-year longitudinal analysis of ART adherence, alcohol use and depressive symptoms measured in daily text-message assessments demonstrated that neither alcohol use nor depressive symptoms alone predicted ART adherence. However, the intersection of alcohol use on days when experiencing depressive symptoms did significantly predict ART non-adherence, for both moderate and heavy alcohol drinkers. Findings suggest that the co-occurrence of alcohol use and depressive symptoms is a robust predictor of poor HIV treatment outcomes.